Phase and surface area studies of maghemite nanoparticles dispersed in silica gel. (8th December 2014) - Ang, B. C.; Yaacob, I. I.; Wong, Y. H.
<x content-type="archive" xml:space="preserve">Abstract</x> First, the superparamagnetic maghemite nanoparticles were synthesised using Massart's procedure. Then, the nanocomposites of the synthesised maghemite nanoparticles and silica were produced by dispersing the as-synthesised maghemite nanoparticles into the silica xerogel prepared by sol–gel technique. The system was then heated for 3 days at 140°C. The phase analysis performed using X-ray diffraction confirmed that the as-synthesised nanoparticles and the nanoparticles within the silica gel were maghemite. Surface characteristic of the nanocomposite was evaluated by N2 adsorption. The 'pure' silica gel and maghemite nanoparticles showed high values of surface area (150–160 m2 g−1), while the surface area of nanocomposite was less than 40 m2 g−1. This was probably due to the formation of dense structures caused by incorporation of maghemite nanoparticles within the pores of silica gel. The pore width increased with increasing content of maghemite nanoparticles.